Does Distance Still Matter? Geographic Proximity and New Product Development - Ganesan, Shankar; Malter, Alan J.; Rindfleisch, Aric (Journal of Marketing, 2005)
Many firms rely on external organizations to acquire knowledge that is useful for developing creative new products and reducing the time needed to bring these products to market. Cluster theory suggests that this knowledge is often obtained from organizations located in close geographic proximity. Specifically, proximity is assumed to foster heightened face-to-face communication, strengthened relational ties, increased knowledge acquisition, and enhanced new product outcomes. The authors identify the limitations of these assumptions and offer an enriched model of the influence of geographic proximity on new product development, which they test using both a cross-sectional survey of 155 firms in the U.S. optics industry and a longitudinal follow-up survey of 73 of these firms. They find that firms located in close proximity engage in increased face-to-face communication, but this communication has little effect on the acquisition of the types of knowledge that lead to enhanced new product outcomes. In contrast, they find that e-mail communication leads to both enhanced new product creativity and development speed. In addition, they find that relational ties moderate rather than mediate the path connecting geographic proximity and new product outcomes. These findings imply that the new product development outcomes typically ascribed to close geographic proximity may actually be attributed to strong relational ties.